A Novel Agricultural Wastes Based Green Glaze - Noor Aznin, Kosmin; Nurul Aimie, Abd Malek (Universiti Sains Malaysia, 2010)
Noor Aznin Kosmin and Nurul Aimie Abd Malek won gold at National Research and Innovation Competition (NRIC) 2010, 26th - 28th May 2010 was held at Dewan Utama Pelajar, located at USM Main Campus, Penang, Malaysia. Organized by the Student Representative Council of Universiti Sains Malaysia.